ChemInform Abstract: Hypervalent Iodine(III) Catalyzed Oxidative C—N Bond Formation in Water: Synthesis of Benzimidazole‐Fused Heterocycles. Issue 5 (February 2015) - Rao, D. Nageswar; Rasheed, Sk.; Vishwakarma, Ram A.; Das, Parthasarathi
Abstract One of the rare examples in which water is used as a solvent in hypervalent iodine(III) catalyzed oxidative C—N bond formation is described.